Liquidity and Stock Returns: Evidence from the UK Market - Tang, Zhiying (2009)
Following Amihud and Mendelson (1986) and Datar et al. (1998), most empirical evidence from US market reveal that stock returns should be an increasing function of bid-ask spread and a decreasing function of turnover rate, confirming the existence of a positive liquidity premium. This paper conducts a detailed analysis of liquidity effect on stock returns in the UK stock market over period January 1993 to December 2008. The results from the cross-sectional regression approach reveals a significant positive return-spread relation limited to the month of January only, confirming the evidence of Eleswarapu and Reinganum (1993). Conflicted with the majority of the existing literature (e.g., Datar et al., 1998), a highly significant but positive return-turnover relationship is evident. This liquidity effects persists even after controlling for the size and book-to-market effect. The time-series regression analysis shows weak evidence of liquidity premium associated with both bid-ask spread and turnover rate, robust to subperiod and seasonality analysis. With regard to the conflicting results with the existing literature, I argue that both bid-ask spread and turnover rate to be poor liquidity proxies, or the US evidence may not be a world-wide phenomenon.